Leading in Switzerland and Poland: A case study of leadership practices in financial services - Marc Steinmann; Carlo Pugnetti (International Journal of Financial Studies, 2021)
Leading across national borders is a challenge, partly due to the cultural differences among employees in different locations. We investigate this dynamic for employees of a Swiss financial services company located in Switzerland and in Poland by surveying employees about their leadership expectations and experiences, as well as about their cultural values. We find that the leadership expectations of employees in these two locations do not differ significantly. However, their experience does, indicating the opportunity for further development of local Polish management practices and leadership behavior, and underlying the importance of local leadership development. In addition, we find that a few cultural dimensions have a significant impact on leadership expectations in both countries, indicating the opportunity to further refine situational leadership behavior throughout the organization independently of location. While organizations spanning across Western and Central European locations need to deal with significant differences in cultural and leadership expectation, our results suggest that they can effectively align leadership practices and thus mitigate the practical challenges arising from these differences.
Keywords: F23; M14; M16; 330; culture; leadership; near-shoring